Value within otolaryngology: Assessment of the cost-utility analysis literature - Krupa R. Patel (KeAi Communications Co., Ltd., 2016)
Objective: To assess the characteristics and quality of cost utility analyses (CUA) related to otolaryngology within the CEA registry and to summarize their collective results. Methods: All cost-utility analyses published between 1976 and 2011 contained in the Cost-Effectiveness Analysis Registry (CEA Registry) were evaluated. Topics that fall within the care of an otolaryngologist were included in the review regardless of the presence of an otolaryngologist author. Potential associations between various study characteristics and CEA registry quality scores were evaluated using the Pearson product moment correlation coefficient. Results: Sixty-one of 2913 (2.1%) total CUA publications screened were related to otolaryngology. Eighteen of 61 (29.5%) publications included an otolaryngologist as an author. Fourteen studies agreed on the cost effectiveness of at least unilateral cochlear implantation and six of seven (85.7%) studies demonstrated the cost effectiveness of continuous positive airway pressure (CPAP) for obstructive sleep apnea (OSA). Forty-six percent (28 of 61) of all manuscripts were published between 2008 and 2011. A more recent publication year was associated with a higher CEA registry quality score while the presence of an otolaryngologist author and journal impact factor had no significant correlation with the quality of the CUA. Conclusion: Based on current evidence in the CEA registry, unilateral cochlear implantation for hearing loss and CPAP for OSA are both cost-effective therapeutic interventions. Although CUAs in otolaryngology have increased in quantity and improved in quality in more recent years, there is a relative lack of CUAs in otolaryngology in comparison to other subspecialties. Keyword: Cost-utility analysis